Long-term survival of two dogs after mitral valve plasty (Veterinary Science Development, 2017)
Two small 9-year-old dogs received mitral valve plasty (MVP) for severe mitral regurgitation that could not be controlled via drug administration. MVP consisted of chordal reconstruction using expanded polytetrafluoroethylene (ePTFE) sutures and semicircular suture annuloplasty using polypropylene sutures. In both cases, the clinical signs dramatically improved after MVP, although postoperative echocardiography revealed slight residual mitral regurgitant flow. Both dogs survived for several years after MVP without any signs of cardiac distress; one dog survived for 9 years and 1 month, and the other dog survived for 7 years and 10 months. These findings highlight the durability of ePTFE sutures as artificial chordae and the excellence of semicircular suture annuloplasty in small dogs.